Ameliorative effect of nerolidol on cyclophosphamide‐induced gonadal toxicity in Swiss Albino mice: Biochemical‐, histological‐ and immunohistochemical‐based evidences. (12th February 2020) - Iqubal, Ashif; Syed, Mansoor Ali; Najmi, Abul Kalam; Ali, Javed; Haque, Syed Ehtaishamul
Abstract: Cyclophosphamide (CP) is commonly used as antineoplastic and immunosuppressant drug with noticeable gonadotoxic profile. Nerolidol (NER) is a sesquiterpene with potent antioxidant and anti‐inflammatory properties. Thus, the present study was designed to explore its possible gonadal protective potential against cyclophosphamide‐induced testicular, epididymal, seminal and spermatozoal toxicities. Animals were divided into five groups: control (normal saline for 14 days), treatment group (NER 200 and 400 mg/kg, p.o) for 14 days along with a single dose of cyclophosphamide (200 mg/kg, i.p) on 7 th day, toxic and Per se groups (cyclophosphamide 200 mg/kg i.p) on 7 th day and NER 400 mg/kg for 14 days respectively. Animals were sacrificed on the 15 day, and body weight, weight of reproductive organs, testosterone level, sperm count, biochemical parameters, histopathological and immunohistochemical studies were performed in the testes, epididymis and in the serum. CP administration induced oxidative stress, nitrative stress, inflammation, reduced testosterone level, sperm count, increased expression of MPO and caused histological aberrations in the testes, epididymis and seminal vesicles. CP caused reduced sperm count, sperm motility and testosterone level which got reversed upon treatment with nerolidol in a dose‐dependent manner. Nerolidol thus acted as a gonadoprotective molecule and prevented the gonadotoxicity of CP.